PENAWARAN SAHAM PERDANA: PENGALAMAN DI BURSA EFEK JAKARTA 1990 â 1998 - Rodoni, Ahmad (Journal of Indonesian Economy and Business, 2002)
This study investigates initial and aftermarket performance of initial public offering (IPOs) for both short term and long term in the Jakarta Stock Exchange (JSE), from January 1990 to December 1998. This study considers market situation at the time of the issuance of IPOs. The short term performance measure of IPOs is tested using daily closing return (Rct), opening return (Rot), offering price to opening price, offering price to closing price and opening price to closing price criteria. The long term aftermarket performance of IPOs is measured using cumulative abnormal returns analysis, buy and hold market adjusted compounded returns, wealth relative, offering price to closing price and opening price to closing price. Using a sample of 233 IPOs in the Jakarta Stock Exchange (JSE), this study finds an average initial (offer-to-open) return of 10.948 percent (10.912 % adjusted return). The findings reveals a lower expected return from those found in developing and several developed markets. The short term aftermarket mean return based on daily closing mean return (Rct), opening mean return (Rot) and opening price to closing price, indicates that benefits of initial performance do not accrue to the secondary market traders. This result is consistent with studies of Barry and Jennings (1993) on the U.S. markets and Yong (1997) on the Malaysian market. The long run aftermarket performance of IPOs is found to be negative. This finding is supported by many IPOs results in the literature.Keywords: Opening-closing mean return, performance of IPO.